SAP30 deacetylates the Tas protein to inhibit PFV replication - Chenchen Wang; Junshi Zhang; Yali Xu; Jiawei Zhao; Manman Qiu; Xingli Zhao; Guoqiang Li; Wentao Qiao; Juan Tan (Cell & Bioscience)
Abstract Background Foamy viruses (FVs), a unique class of retroviruses, establish lifelong latent infections in the host without causing symptoms, contributing to the relatively slow progress in FV research. However, key mutations in FVs can result in severe consequences due to their broad cellular tropism, underscoring the importance of studying latent FV infections. Results To identify new host proteins involved in the replication of prototype foamy virus (PFV), we previously infected the human fibrosarcoma cell line HT1080 with PFV and performed transcriptomic sequencing. The analysis revealed a significant upregulation of SAP30 mRNA levels following PFV infection. Further experiments demonstrated that PFV infection enhances SAP30 promoter activity via the Tas protein, leading to increased SAP30 mRNA and protein expression. Overexpression of SAP30 inhibited PFV replication, whereas knockdown of endogenous SAP30 enhanced PFV replication. Furthermore, SAP30 interacted with the Tas protein to induce its deacetylation, thereby suppressing Tas-mediated transactivation of the PFV LTR and IP promoters. The Sin3 interaction domain at the C-terminus of SAP30 was identified as the critical domain for inhibiting PFV transcription. Conclusions Our findings suggest that SAP30 inhibits PFV replication by deacetylating the Tas protein, thereby disrupting its transcriptional activation function. Key words: prototype foamy virus; SAP30; Tas; transcription; deacetylation.